Environmental factors influencing the distribution of habitat types in the highlands of the Kamnik − Savinja Alps. (7th July 2022) - Škornik, Sonja; Paušič, Igor; Novak, Tone; Janžekovič, Franc; Ivajnšič, Danijel; Tostovršnik, Mihaela; Kozel, Peter
Abstract: In this work, we investigated the relationship between habitat types (HTs) and selected environmental factors in the highlands at altitudes of 1800–2558 m in the Kamnik-Savinja (KS) Alps in Slovenia. For 275 sampling sites, we identified seven HTs in their typical form and 11 ecotones, and provided field and modelled data for 14 environmental factors. HTs-environment relationships were analysed using multivariate ordination methods. In addition, binomial generalised linear mixed models were applied to reveal the influence of environmental factors on the occurrence of most frequent HTs in the study area [Outer Alpine Pinus mugo scrub (EUNIS code F2.4/Natura 2000 code 4070*), Southern rusty sedge grasslands (E4.413/6170), Cushion sedge carpets (E4.433/6170) and Fine calcareous screes (H2.43/8120)]. Results showed that certain modelled data (e.g. average annual air temperature) combined with field measurements (e.g. inclination, soil surface and soil moisture) can be effective predictors of most representative HTs in the study area, and thus useful for further refining of monitoring. Our study contributes to the knowledge and understanding of the relationships between environmental conditions and the occurrence of highland HTs in KS Alps, which probably concerns a great part of the Alpine highlands. Such knowledge is essential for assessing credible long-term conservation planning.